Emergence of urban malaria and the associated risk factors: a case–control study in Mutare city, Zimbabwe - Sungano Mharakurwa; Natasha Mbwana; Trish Mharakurwa; Thelma Karumbidza; Vuyisile Mathe; Punha Fusire; Andrew Tangwena; Wilson Chauke; Munyaradzi Mukuzunga; Patience Dhliwayo; Shungu Mtero Munyati; Lovemore Gwanzura; et al. (Malaria Journal)
Abstract Background Mutare city of Zimbabwe was considered free of autochthonous malaria, until 2017, when the Ministry of Health and Child Care formally confirmed escalating cases of locally transmitted malaria in the city. The current study examined the risk factors for malaria cases in the city to aid in formulation of targeted intervention packages for helping restore malaria-free status. Methods The study employed complementary cross-sectional and case–control designs to ascertain the magnitude and risk factors of urban malaria cases presenting at all eight primary health care facilities of Mutare city from 2022 to 2023. Malaria cases were enrolled as confirmed by RDT or microscopy on presenting all-age symptomatic suspected malaria patients. Controls were similarly enrolled as all-age symptomatic suspected malaria patients found negative by both RDT and microscopy. All cases and controls were enrolled as representative of the presenting population with no matching. Data were analysed for descriptive and prevalence statistics, as well as risk factors, using SPSS Faculty version 27. Results In a multivariate binary logistic model, significant risk factors for malaria cases found in the city included residential locale (RR [95%CI]: 3 [1.1–5.8], p = 0.029, N = 7,222), household proximity to still surface water pools or unprotected wells (16 [3.8–67.5], p < 0.001) and travel history in the past 2 weeks (9 [5.2–14.4], p < 0.001, N = 7,222), modal travel destinations being malaria-endemic adjoining districts within Zimbabwe, as well as areas of neighbouring Mozambique, mainly for trade or work. By far the most predominant risk factor for malaria cases was artisanal mining (RR [95%CI]: 22 [10.7–44.1], p < 0.001), which was 93% dominated by men, and male residents exhibited four-fold higher odds of being malaria cases than females (4 [2.0–6.5]). Conclusions Significant risk factors for urban malaria were found that were consistent with both autochthonous transmission and imported malaria in Mutare city. Environmental management and the deployment and concomitant promotion of mass ITNs, personal protection and other intervention packages, especially targeting communities exposed to the identified risk factors, would be instrumental towards re-establishing urban malaria elimination from Mutare city.